Software Business Start-up Memories Key Decisions in Success Stories - Cann, Roderick van. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Describes the decisions that led to the success of 16 software companies. The decisions are illustrated in detail, providing entrepreneurs with insights into what it takes to make a decision that can change the future of a company.